RANCANGAN BUKU KERJA PENGUATAN PENGETAHUAN MATERI BAGI GURU BIOLOGI SMA (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: Technological Pedagogical and Content Knowledge (TPACK) is a conceptual framework that shows the relationship between three kinds of knowledge needed by the teacher or prospective teacher including technological knowledge, pedagogical knowledge, and content knowledge. The research putposes was to knowed the quality of workbook of Content Knowledge (CK) for Stregthening Teacher of Biology Competencies. The workbook was developed from essential indicator of Teacher Biology Competency Test. Design, develop, simulation and validation of workbook by internal validator conducted at Biology Education Faculty of Teacher Training and Education University of Riau. External validation and second validation of the workbook is in MGMP Biology SMA Pekanbaru. Workbook validated on four aspects include format, content, illustrations and language. The result of format aspect is 3,42 with very valid categories, content is 3,40 with very valid categories, ilustration is 3,40 with very valid categories, and language is 3,44 with very valid categories. The result of whole aspecs are 3,41with very valid categories that meaning the workbook can be used as a learning resource by the teachers to improve content competencies and learning proces.Keywords: Biology Teacher, Content Knowledge, Workbook.